2017
DOI: 10.1080/15384047.2017.1294289
|View full text |Cite
|
Sign up to set email alerts
|

Presence of novel compound BCR-ABL mutations in late chronic and advanced phase imatinib sensitive CML patients indicates their possible role in CML progression

Abstract: BCR-ABL kinase domain (K D ) mutations are well known for causing resistance against tyrosine kinase inhibitors (TKIs) and disease progression in chronic myeloid leukemia (CML). In recent years, compound BCR-ABL mutations have emerged as a new threat to CML patients by causing higher degrees of resistance involving multiple TKIs, including ponatinib. However, there are limited reports about association of compound BCR-ABL mutations with disease progression in imatinib (IM) sensitive CML patients. Therefore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…In this cohort, the percentage of males increased from 59.1% to 81.8% when comparing groups A and B. This gender distribution was also observed in other studies, which indicated that regular detection of ACAs and/or KD mutations was more important in male patients …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this cohort, the percentage of males increased from 59.1% to 81.8% when comparing groups A and B. This gender distribution was also observed in other studies, which indicated that regular detection of ACAs and/or KD mutations was more important in male patients …”
Section: Discussionsupporting
confidence: 86%
“…This gender distribution was also observed in other studies, which indicated that regular detection of ACAs and/or KD mutations was more important in male patients. 5,7 In conclusion, we confirmed the role of ACAs and/or KD mutations in CML progression and demonstrated that both of these abnormalities…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…DNA was isolated from collected blood samples by using GeneJET Genomic DNA Purification Kit (ThermoFisher Scientific CAT# K0721) following manufacturer's instructions. This was followed by the integrity check of isolated DNA through Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) gene amplification 17 , 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Chronic myeloid leukemia (CML) is a clonal malignant proliferative disease of hematopoietic stem cells (HSCs). e main hallmark is the formation of BCR-ABL fusion gene at the molecular level [1]. BCR-ABL is a chimeric oncogene arising from t (9; 22) (q34; q11) chromosomal translocation.…”
Section: Introductionmentioning
confidence: 99%